Speech Delay in Early Childhood: A Case Study of a 3.5-Year-Old Child - Nurkhamidah, Neni; Mutadho, Fathiaty; Rafli, Zainal (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study examines the speech development of SY, a 3.5-year-old child with speech delay, living in a bilingual environment with early exposure to screen time. Through a case study approach, data was collected via observations, interviews with SY's mother and therapist, and therapy records. Initially, SY displayed significant speech limitations, including omitting sounds, using incomplete words, and having a limited vocabulary. Factors such as frequent screen exposure and reduced direct interaction were identified as potential contributors to SY's speech delay. After six months of Speech-Language Therapy (SLT) led by an experienced therapist, SY has shown improvements in word completion, clearer articulation, vocabulary expansion, and social engagement. However, challenges remain in maintaining SY's focus during therapy sessions, a common issue for children his age. The study underscores the importance of early intervention, reduced screen time, and increased face-to-face communication in managing speech delays. Findings suggest that a structured therapy approach combined with supportive family interactions can effectively foster language development in young children, even in bilingual settings, reinforcing the role of active parental involvement in enhancing communication outcomes.